La direction des sociétés anonymes en droit sénégalais compaée aux droits français anglais et américain - Dieng, Françoise (Université Paris 1, 1995)
Le Sénégal, par la loi n°85-40 du 29 juillet 1985, s'est doté de son premier code des sociétés commerciales depuis son accession à l'indépendance. Cette loi s'inspire des droits français, anglais et américain quant à la direction des sociétés anonymes. C'est à ces droits que sera comparée la direction des sociétés anonymes en droit sénégalais en ses divers aspects que sont les pouvoirs des dirigeants sociaux, leur statut juridique leurs devoirs et leur responsabilité.
Keywords: Approche comparée; Droit commercial; Droit comparé; Droit des sociétés commerciales; Sociétés anonymes; Sénégal

Un sujet de droit original et particulier : le consommateur : contribution à l'étude de la notion de volonté contractuelle en droit interne - Delplanque, Hervé (Université de Valenciennes et du Hainaut-Cambrésis, 1995)
No abstract in English
Issue: 1995VALE0028
Keywords: Consommateur; Consumer; Droit privé; Private law

La situation des créanciers gagistres dans les procédures collectives - James, Jean-Claude (Université de Bourgogne, 1995)
La loi du 25 janvier 1985 oriente clairement le droit des procédures collectives vers le sauvetage des entreprises en difficulté. Le législateur s'est donc efforce de réduire les droits des créanciers munis de suretés réelles spéciales, au nombre desquels figurent les créanciers gagistes. Il s'attaque ainsi à l'existence des suretés en favorisant leur annulation ou leur substitution par une autre garantie. Il poursuit en outre l'extinction ou l'amputation systématique des créances garanties. Enfin les créanciers nantis ne peuvent plus exercer librement leur droit de réalisation forcée du gage, encore moins leur droit de préférence, cependant ces atteintes sont compensées par l'éclatement des techniques de réalisation du gage. Celles-ci permettent d'éluder la loi du concours. Mais elles révèlent aussi d'importantes disparités entre les créanciers gagistes.
Keywords: Assurance; Débiteur et créancier; Entreprise en difficulté; Gage; Liquidation judiciaire; Procédures collectives; Redressement judiciaire; Sociétés; Sûretés

Omskrywing en funksies van die fisiese beheerelement in die sakereg - Van Oosten, Hendrina (University of South Africa, 1995)
In hierdie ondersoek is daar navorsing gedoen oor die aard en rol van fisiese beheer in die sakereg met die oog daarop om dit te omskryf en die funksies daarvan te identifiseer. By die verkryging van eiendomsreg word net vereis dat die fisiese beheer wat ten aansien van die saak uitgeoefen word, effektief moet wees. Of 'n saak effektief beheer word al dan nie, word aan die hand van die heersende verkeersopvattings getoets. Hierdie verkeersmaatstawwe wat in die praktyk ten aansien van bepaalde soorte sake uitgekristalliseer het, is buigsaam en veranderlik en dit maak dit moontlik dat die reg by maatskaplike en ekonomiese veranderinge aanpas. Die funksie van fisiese beheer in gevalle van verkryging is altyd publisiteit. In die geval van die beskerming van eiendomsreg word fisiese beheer besonder breed omskryf en daar word slegs verwag dat die persoon van wie die saak teruggeeis word, genoegsame beheer daaroor moet he om dit te kan teruggee. Die funksie van beheer is hier suiwer funksioneel. By die verlies van eiendomsreg speel fisiese beheer nie juis 'n besondere rol nie aangesien die verlies van beheer nie noodwendig op die verlies of beeindiging van eiendomsreg dui nie. Wanneer dit wel ter sprake kom, is die funksie daarvan publisiteit. In die geval van die verkryging van besit en houerskap, dien daarop gelet te word dat die enigste vereiste is dat beheer effektief moet wees en dit word weer eens aan die hand van verkeersmaatstawwe bepaal. Fisiese beheer word strenger omskryf vir verkryging as vir behoud. By die beskerming van besit en houerskap is die enigste vereiste wat gestel word dat beheer vreedsaam en ongestoord moes gewees het. Wanneer beheer oor 'n saak verloor word, gaan dit gewoonlik gepaard met die verlies van besit of houerskap. Die funksie van fisiese beheer is deurgaans publisiteit. Fisiese beheer word redelik streng omskryf vir doeleindes van 'n gewone pand en daar word gewoonlik vereis dat die pandsaak gelewer en gehou moet word vir die vestiging en behoud van 'n pandreg. Die funksies van beheer is hier sekuriteit en publisiteit.
Keywords: Direct control; Droit de la propriété; Effective control; Immediate control; Indirect control; Joint control; Mediate control; Ownership; Physical control; Publicity

Fiduciary duties of company directors with specific regard to corporate opportunities - Havenga, Michele Kyra (University of South Africa, 1995)
South African company law is currently the object of comprehensive review. One o f the areas under scrutiny is that of corporate governance. Control over management is vital in the interests of the company itself, its shareholders and its creditors. Effective accountability should be balanced against the need to allow those who manage a certain measure of freedom and discretion in the exercise of their function. Company directors are subject to various duties. This thesis concentrates on their fiduciary obligation. It is suggested that this sui generis obligation is owed to the company as a separate entity. Interests of other groups may sometimes merit con sideration. Against the background of a comparative investigation, a "corporate opportunity" is defined as any property or economic opportunity to which the com pany has a claim. South African law protects a company’s claim to an opportunity if it is in the company’s line of business and if the company has justifiably been relying upon the director(s) to acquire it or to assist in its acquisition for the company. The application of established fiduciary principles suffice to resolve corporate opportunity matters. Essentially the application of these rules amount to a determination whether the director has complied with his fundamental duty to act in the company’s best interests. There seems to be no need for a separate doctrine of corporate opportunities.' A director should only be absolved from liability on account of the company’s inability to pursue an opportunity or its rejection by the company if there was no real conflict of interest. The appropriation of corporate opportunities should not be ratifiable, both because the ratification constitutes a fraud on the minority, and because the decision to ratify cannot be regarded as being in the interests of the company. The relationship between the appropriation of corporate opportunities, misuse of confidential information and competition is investigated. These aspects fre quently overlap, but should be distinguished because their bases, and accordingly their appropriate remedies, may differ. Effective control may benefit by a restatement of directors’ fiduciary duties in the Companies Act. To this end certain amendments to the Act are recommended.
Keywords: Codes of conduct; Competition; Confidential information; Conflicts of interest; Corporate opportunities; Corporate opportunity doctrine; Corporation law; Directors of corporations; Fiduciary duties; Multiple directorships; Secret profits

Rethinking International Bankruptcy Law: A Critical Study of the Substantive and Procedural Approaches to its Current Status. Vol. 1 - Al-Bashir, Salah-eddin M. (McGill University, 1995)
This dissertation is essentially a critical examination of the traditional and reformatory approaches of international bankruptcy law in Canada, England, and the United States. It highlights the shortcomings of the traditional law and the inherent limitations, contradictions, and inconsistencies of its applicable mechanism; the doctrines of private international law. The dissertation further argues that the reform schemes thus far advanced suffer from jurisdictional problems and fall short of ensuring optimal outcomes for international bankruptcy cases. Although some of these reform schemes achieve the desired equality of distribution, they unnecessarily entail a reduction in the value of distributable assets by carrying out piecemeal liquidations of local assets in order to satisfy some local claims. […] Cette thèse contient principalement une étude critique des conceptions traditionnelles et réformatrices de la loi sur la faillite internationale au Canada, en Angleterre et États-Unis. Elle éclaire les insuffisances de la loi traditionnelle ausi qua les limitations, contradictions et incohérences des mécanismes qui lui sont inhérents: les principes du droit international privé. Cette thèse soutient en outre que les plans de la reforme formulés jusque-là sont affectés par des problèmes d'organisation judiciaire et n'aboutissent pas à assurer les meilleurs résultats pour les procédures de faillite internationale. Quoique certains de ces projets de réforme réalisent l’égalité de distribution recherchée, ils entrainent une diminution inutile de la valeur des biens distribuables en provoquant des liquidations fragmentaires de biens situés sur place, en vue de satisfaire certaines réclamations locales. […]
Identifier: https://escholarship.mcgill.ca/concern/theses/8c97kv575
Keywords: Bankruptcy; Insolvency

Rethinking International Bankruptcy Law: A Critical Study of the Substantive and Procedural Approaches to its Current Status. Vol. 2 - Al-Bashir, Salah-eddin M. (McGill University, 1995)
This dissertation is essentially a critical examination of the traditional and reformatory approaches of international bankruptcy law in Canada, England, and the United States. It highlights the shortcomings of the traditional law and the inherent limitations, contradictions, and inconsistencies of its applicable mechanism; the doctrines of private international law. The dissertation further argues that the reform schemes thus far advanced suffer from jurisdictional problems and fall short of ensuring optimal outcomes for international bankruptcy cases. Although some of these reform schemes achieve the desired equality of distribution, they unnecessarily entail a reduction in the value of distributable assets by carrying out piecemeal liquidations of local assets in order to satisfy some local claims. […] Cette thèse contient principalement une étude critique des conceptions traditionnelles et réformatrices de la loi sur la faillite internationale au Canada, en Angleterre et États-Unis. Elle éclaire les insuffisances de la loi traditionnelle ausi qua les limitations, contradictions et incohérences des mécanismes qui lui sont inhérents: les principes du droit international privé. Cette thèse soutient en outre que les plans de la reforme formulés jusque-là sont affectés par des problèmes d'organisation judiciaire et n'aboutissent pas à assurer les meilleurs résultats pour les procédures de faillite internationale. Quoique certains de ces projets de réforme réalisent l’égalité de distribution recherchée, ils entrainent une diminution inutile de la valeur des biens distribuables en provoquant des liquidations fragmentaires de biens situés sur place, en vue de satisfaire certaines réclamations locales. […]
Identifier: https://escholarship.mcgill.ca/concern/theses/8c97kv575
Keywords: Bankruptcy; Insolvency

La personnalité morale en droit privé comparé : l'unité du concept et ses applications pratiques - Allemagne, Angleterre, Belgique, Suisse, Etats-Unis, France, Italie, Pays-Bas et Suisse - Simonart, Valérie (Bruylant, 1995)